Working Mechanism Analysis of a Rotating Translational Integrated Mechanical Device - Huiyong Zhao; Yaocheng Zhang; Zhaojian Yang (Jixie chuandong)
A rotating and translating integrated mechanical device is designed. The structure，principle and main components of the device are introduced in detail，and the force acting on the mechanism is analyzed. Taking its application in winch as an example to solve the problems of wire rope disorder and rope biting in winch，the relevant type selection design is carried out. The three-dimensional model of the mechanism is established by UG， and kinematics simulation analysis of the rotating and translating integrated mechanism is carried out by Adams. The rotational speed，speed and displacement diagrams of the main components are obtained，and through comparing with the value calculated by theory，it is concluded that the mechanism can meet the functional requirements， the feasibility and accuracy of the mechanism are verified.